Desenvolvimento de um aplicativo para simulação de um laboratório virtual de ensino de química (LabQuins) - PANTOJA NETO, Pedro Viana (2024)
Information and communication technology has effectively established itself from the creation of new products that increasingly help the citizen's daily life. Increasingly, through technological means in the form of smartphones, people are using software-based solutions as alternative tools to assist in their daily lives. In the context of teaching, the combination of such tools with the application of gamification concepts is an alternative way to improve the quality of teaching and, consequently, the learning of young people. With that in mind, an application was created that aims to teach chemistry in a virtual way, that is, presenting elements that constitute a real laboratory. To validate the software's capacity as a teaching support tool, it was submitted to use by higher education students. The results indicate that LabQuins can function as a teaching support tool.